Dynamic geovisualization of population expected at points of interest over daily timescales: an application at Latsia, Nicosia, Cyprus - Chrysoulidis, Savvas; Kyriakidis, Phaedon (My University, 2019)
The subject of human security is individual security. Each person has a unique geospatial profile (Spatial Identity) which is dynamic in spatio-temporal terms. The geospatial profile refers to the characteristics/elements of each person's daily activities and particular the spatio-temporal footprint of these activities within the physical (natural) and human environment. Individuals with common geospatial profiles create similar behavioral group profiles. The activities of each group of people could be studied as daily moves of individuals. The mobility behavior of individuals on an hourly, daily, weekly or yearly basis consists of few or more posts, the main difference being the duration of the time that individuals spend at these posts. The time spent at these positions varies from few tenths of a second up to hours. More critical for security issues are those places/positions where people spend more time. These predefined concentration points/structures constitute Points of Interests (POIs), which act as concentrating places for individuals with common geospatial profile characteristics for specified time periods. This paper explores how 3D visualization of an individuals' position, postulated on the basis of existing spatiotemporal qualitative and quantitative datasets from selected POIs, could provide an additional decision-making tool for public security authorities-first responders in the context of an operational plan/strategy in crisis and disaster management situations or even for minor threats such as car accidents causing traffic jams.
Keywords: Complex Environment; First Responders; Geospatial Profile; Geovisualization; Human Security; Point of Interest; Security Stakeholders